1999
DOI: 10.1016/s0896-6273(00)80732-1
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of EphA Receptor Function by Coexpressed EphrinA Ligands on Retinal Ganglion Cell Axons

Abstract: The Eph family is thought to exert its function through the complementary expression of receptors and ligands. Here, we show that EphA receptors colocalize on retinal ganglion cell (RGC) axons with EphA ligands, which are expressed in a high-nasal-to-low-temporal pattern. In the stripe assay, only temporal axons are normally sensitive for repellent axon guidance cues of the caudal tectum. However, overexpression of ephrinA ligands on temporal axons abolishes this sensitivity, whereas treatment with PI-PLC both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
244
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(265 citation statements)
references
References 36 publications
19
244
1
Order By: Relevance
“…We investigated ephrinA5 protein expression in the retina and detected a high expression in the nasal part compared to the temporal one. This result is in accordance with the previously described retinal ephrinA5 expression pattern in the chick [51] and with ephrinA5 mRNA expression found in a high-nasal-to-low-temporal gradient in the developing mouse embryo retina [52]. As previously described, the mouse retinal ganglion cells also expressed EphA5 and EphA6 receptors [53].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We investigated ephrinA5 protein expression in the retina and detected a high expression in the nasal part compared to the temporal one. This result is in accordance with the previously described retinal ephrinA5 expression pattern in the chick [51] and with ephrinA5 mRNA expression found in a high-nasal-to-low-temporal gradient in the developing mouse embryo retina [52]. As previously described, the mouse retinal ganglion cells also expressed EphA5 and EphA6 receptors [53].…”
Section: Discussionsupporting
confidence: 92%
“…However, it is unlikely that the co-expression of ligand and receptor in the same region of the visual system is responsible of an attractive mechanism, since it has been extensively shown, using in vitro studies and double ephrinA2/ephrinA5 knock-out mice [30,48-50], that the topographic map of the visual system is established by a chemorepellent activity of ephrinAs [50]. Nevertheless, it may be that ligands and receptors are present on the same cells, as it has been shown in the chick retinal ganglion cells, where ephrinA2, ephrinA5 and EphA5 mRNA are co-expressed [51]. In this case, the presence of ephrinA-ligand on the retinal ganglion cells could control the EphA-receptor function through a modulation of its intracellular signalling pathway [51] as discussed above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly though, different Eph receptors and ephrins are often co-expressed by the same cells raising the question about potential interactions in cis (within the same cell) affecting the functional signaling in trans (between the opposing cells). The in-cis-interaction theory gained momentum after several reports indicated that the responsiveness of EphA expressing retinal axons is negatively modulated by A-class ligands expressed on the same cells [43,44]. Interestingly, a seemingly contradictory conclusion was published by Marquardt, Pfaff and colleagues [45], who documented that at least in spinal motor neurons coexpressed Ephs and ephrins segregate laterally into distinct membrane domains from which they induce opposing effects: EphAs direct growth cone collapse/repulsion, while ephrin-As signal motor axon growth/attraction.…”
Section: Eph/ephrin Interactions On the Surface Of The Same Cellmentioning
confidence: 99%
“…This protocol was adapted by various research groups for their experimental designs and, for these modifications, we would like to refer throughout the manuscript to the relevant primary research literature 5,6,9,10,14,18,33 . First we describe the guidance behavior of axons from chick retinal ganglion cells (RGCs) growing on carpets consisting of alternating membrane fractions derived from anterior and posterior chick optic tecta (original version, Step 1A of PROCEDURE).…”
Section: Introductionmentioning
confidence: 99%